Intraindividual Embryo Morphokinetics Are Not Affected by a Switch of the Ovarian Stimulation Protocol Between GnRH Agonist vs. Antagonist Regimens in Consecutive Cycles - Dietrich, Jens E.; Freis, Alexander; Beedgen, Franziska; von Horn, Kyra; Holschbach, Verena; Liebscher, Julia; Strowitzki, Thomas; Germeyer, Ariane (Frontiers in Endocrinology, 2020)
Background The impact of controlled ovarian stimulation (COS) during medically assisted reproduction (MAR) on human embryogenesis is still unclear. Therefore, we investigated if early embryonic development is affected by the type of gonadotropin-releasing hormone (GnRH) analogue used to prevent a premature LH surge. We compared embryo morphology and morphokinetics between GnRH agonist and antagonist cycles, both involving human chorionic gonadotropin (hCG)-trigger. To reduce possible confounding factors, we used intraindividual comparison of embryo morphokinetics in consecutive treatment cycles of the same patients that underwent a switch in the COS protocol. Methods This retrospective cohort study analyzed morphokinetics of embryos from patients (n= 49) undergoing a switch in COS protocols between GnRH agonists followed by GnRH antagonists, or vice versa, after culture in a time-lapse incubator (EmbryoScope®, Vitrolife) in our clinic between 06/2011 and 11/2016 (n= 49 GnRH agonist cycles with n= 172 embryos; n= 49 GnRH antagonist cycles with n= 163 embryos). Among time-lapse cycles we included all embryos of the two consecutive cycles before and after a switch in the type of COS in the same patient. In-vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) was performed and embryos were imaged up to day 5. Data were analyzed using Mann-Whitney U test or Fisher’s exact test. The significance level was set to p= 0.05. Patients with preimplantation genetic screening cycles were excluded. Results The mean age (years ± standard deviation) of patients at the time of treatment was 35.7 ± 4.3 (GnRH agonist) and 35.8 ± 4.0 (GnRH antagonist) (p= 0.94). There was no statistically significant difference in the number of oocytes collected or the fertilization rate. The numbers of top quality embryos (TQE), good-quality embryos (GQE) or poor-quality embryos (PQE) were also not different in GnRH agonist versus antagonist cycles. We found no statistically significant difference between the analyzed morphokinetic parameters between the study groups. Conclusions Our finding supports the flexible use of GnRH analogues to optimize patient treatment for COS without affecting embryo morphokinetics.